United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of IAIS Insurance Core Principles. (IMF Staff Country Reports; Country Report, 2010)
This paper discusses key findings of the Detailed Assessment of Observance of International Association of Insurance Supervisors (IAIS) Insurance Core Principles for the United States. Most U.S. insurers write primary insurance on U.S. risks. The U.S. market is characterized by low market concentration in most sectors, indicating a high degree of competition. Overall, the insurance sector, and the property and casualty companies in particular, has been resilient through the financial crisis. However, there have also been significant stresses in the insurance sector in the last two years.